PENINGKATAN KUALITAS PELAYANAN KB SEBAGAI UPAYA PEMBINAAN AKSEPTOR DI KECAMATAN TRUCUK KABUPATEN BOJONEGORO - jurnalmap map; Endah Tri Ratnawati; Hadi Susanto; Arini Sulistyowati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
The purpose of this study is to describe the quality of family planning services and its constraints in the Trucuk District area of Bojonegoro Regency. This type of research is a qualitative descriptive study. Data collection techniques with interview observation and documentation. Processing and data analysis using descriptive analysis. The results showed that the quality of family planning services seen from 1) Tangible has a fairly good room. 2) Reliable is good. 3) Responsiveness provided by officers is good. 4) Assurance of the community is satisfied and happy in using health services. 5) Emphaty given by the officers gives a friendly and pleasant impression. As for the constraints: 1) public knowledge about contraception is still low. 2) low level of community education. 3) KB culture is very low.Keywords: services, family planning